PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK PADA DINAS KOPERASI DAN UMKM KOTA PEKANBARU TAHUN 2014 - Rio Pinondang Hasibuan; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study wanted to see how the process of implementation of procurement of goods and services at the Department of Cooperatives and UMKM. The problem is the background of this research is Pekanbaru City Government in implementing the system of procurement of goods and services in the E-Procurement rated indecisive, this results in the lack of public information on the procurement of goods and services.This research is a qualitative descriptive study, the data collection techniques in this research is descriptive analysis. This research uses documentation (observation) and interview with key informants as an object of information that aims to achieve the goal to have the information in this study. Data used in this study are primary data and secondary data obtained through direct observation and interviews with key informants in this study.Based on the analysis results can be deduced that the announcement of the procurement of goods and services at the Department of Cooperatives and UMKM Pekanbaru is good enough. Department of Cooperatives and UMKM Pekanbaru City had reported all activities on the website page LPSE announced through the Public Procurement Information System Plan (Syrup). But reporting activities that have been carried out no reported, so the accountability of procuring goods and services at the Department of Cooperatives and UMKM rated yet to be done.Keyword: Procurement of goods and services, LPSE, and E-Procurement